Benefits of Chimeric Antigen Receptor T-Cell Therapy for B-Cell Lymphoma - Zhou, Wenyujing; Chen, Weihong; Wan, Xiaochun; Luo, Changru; Du, Xin; Li, Xiaoqing; Chen, Qian; Gao, Ruiwen; Zhang, Xiaohan; Xie, Mei; Wang, Mingjun (Frontiers in Genetics, 2022)
Objective: The aim was to study the benefits and risks of anti-CD19 chimeric antigen receptor (CAR) T-cells in adults with B-cell lymphoma. Methods: From October 2015 to October 2021, we treated five patients with B-cell lymphoma, comprising two with mantle cell lymphoma, one case of Burkitt lymphoma, one case of diffuse large B-cell lymphoma, and one case of chronic lymphocytic leukemia/small lymphocytic lymphoma. The patients were given the FC regimen 5 days before the infusion of anti-CD19 CAR T-cells. The median total number of CAR T-cells infusions was 350*10^6 (88*10^6–585*10^6). Results: 1) Patients who received CAR T-cell induction therapy achieved complete remission (CR) in Case 1 and Case 3 and partial remission (PR) in Case 2. Case 3’s ATM and D13S25 gene deletions were negative 42 days after CAR T-cell therapy, and molecular biology CR (mCR) and minimal residual disease (MRD) were negative for 5 years and 6 months. The patient in Case 3 was cured. 2) Case 4 patient’s TP53 gene mutation became negative 1 month after CAR T-cell therapy. MRD was negative after CAR T-cell therapy at 41 and 42 months in Cases 4 and 5, respectively. 3) Case 1∼Case 3 patients developed cytokine release syndrome (CRS) without encephalopathy syndrome, accompanied with serious adverse events. CRS can be effectively managed with tocilizumab, etanercept, glucocorticoids, and plasmapheresis. Conclusion: Anti-CD19 CAR T-cell therapy is effective in treating relapsed/refractory B-cell lymphoma, and the side effects of CAR T-cell therapy can be properly managed. CAR T-cell therapy has high efficacy and presented no side effects in the treatment of MRD in B-cell lymphoma (NCT03685786, NCT02456350).